Positive electrode for lithium secondary battery and lithium secondary battery including the same
Patent Information
- Application Number
- JP2023544395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-18
- Filing Date
- 2022-10-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-10-27
AI Technical Summary
【0016】 本発明によると、リチウム二次電池の正極に金属酸化物系添加剤を添加することで、正極の容量を向上させて電池の放電容量及び寿命特性を改善させることができる。
Smart Images

Figure 0007631539000002 
Figure 0007631539000003 
Figure 0007631539000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 2021-0159053 dated November 18, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.
[0002] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]
[0003] Recently, the demand for secondary batteries has been increasing due to the rapid development of electronic devices and electric vehicles. In particular, with the trend toward smaller and lighter portable electronic devices, there is a growing demand for secondary batteries with high energy density that can meet the trend.
[0004] Among secondary batteries, lithium-sulfur secondary batteries use sulfur-based compounds with sulfur-sulfur bonds as the positive electrode active material, and carbon-based materials in which insertion and deintercalation of alkali metals such as lithium or metal ions such as lithium ions occurs, or silicon or tin that forms an alloy with lithium as the negative electrode active material. Specifically, they store and generate electrical energy using an oxidation-reduction reaction in which the oxidation number of sulfur decreases as the sulfur-sulfur bond is broken during discharge, which is a reduction reaction, and the oxidation number of sulfur increases during charging, which is an oxidation reaction, and the sulfur-sulfur bond is formed again.
[0005] In particular, sulfur used as the positive electrode active material in lithium-sulfur secondary batteries has a theoretical energy density of 1675mAh / g, which is about five times higher than the positive electrode active material used in existing lithium secondary batteries, making it possible for the battery to achieve high output and high energy density. In addition, sulfur is inexpensive, has abundant reserves, is easy to supply and demand, and is environmentally friendly, so it is attracting attention as an energy source for medium and large devices such as electric vehicles as well as portable electronic devices.
[0006] However, the lithium-sulfur secondary battery has a problem that polysulfides are formed and released from the positive electrode during operation, resulting in a shuttling phenomenon, which causes an irreversible loss of positive electrode active material and reduces the life characteristics of the battery.
[0007] In order to solve the problem of the deterioration of the life characteristics of the lithium-sulfur secondary battery, research is being conducted on adding a polysulfide adsorbent or redox mediator to the positive electrode, or coating the surface of the separator with a polysulfide adsorbent or repelling material.
[0008] For example, Japanese Patent Publication No. 2004-179160 and Korean Patent Publication No. 2015-046861 disclose a positive electrode for a lithium-sulfur secondary battery containing an inorganic additive, but there are some limitations in improving the life characteristics of the battery.
[0009] Therefore, there is a continuing demand for the development of materials that can significantly improve the life characteristics of lithium-sulfur secondary batteries. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Publication No. 2004-179160 [Patent Document 2] Korean Patent Publication No. 2015-0046861 Summary of the Invention [Problem to be solved by the invention]
[0011] The present inventors have confirmed that when niobium tungsten oxide, a metal oxide additive, is added to the positive electrode of a lithium-sulfur secondary battery, the discharge capacity of the positive electrode and the life characteristics of the battery are improved.
[0012] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a positive electrode for a lithium secondary battery having improved discharge capacity and life characteristics.
[0013] Another object of the present invention is to provide a lithium secondary battery including a positive electrode for a lithium secondary battery having excellent discharge capacity and life characteristics. [Means for solving the problem]
[0014] To achieve the above object, the present invention provides a positive electrode for a lithium secondary battery including a positive electrode active material layer, the positive electrode active material layer including a sulfur-carbon composite as a positive electrode active material, a binder, and a metal oxide-based additive.
[0015] The present invention also provides a lithium secondary battery comprising the positive electrode, the negative electrode and an electrolyte. Effect of the Invention
[0016] According to the present invention, by adding a metal oxide-based additive to the positive electrode of a lithium secondary battery, the capacity of the positive electrode can be increased, and the discharge capacity and life characteristics of the battery can be improved. [Brief description of the drawings]
[0017] [Figure 1] 1 is a graph showing the results of measuring the discharge capacity of lithium-sulfur secondary batteries prepared in Example 1 and Comparative Example 1. [Diagram 2] 1 is a graph showing the results of measuring the life characteristics of lithium-sulfur secondary batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will now be described in more detail to aid in understanding the present invention.
[0019] The terms and words used in this specification and claims should not be interpreted in a limited manner based on their ordinary or dictionary meaning, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0020] [Positive electrodes for lithium secondary batteries] The present invention relates to a positive electrode for a lithium secondary battery, the positive electrode including a positive electrode active material layer, the positive electrode active material layer including a sulfur-carbon composite as a positive electrode active material, a binder, and a metal oxide-based additive.
[0021] Specifically, the positive electrode for a lithium secondary battery of the present invention can include a positive electrode current collector; and a positive electrode active material layer formed on at least one surface of the current collector.
[0022] In the positive electrode for a lithium secondary battery according to the present invention, the metal oxide-based additive is included in the positive electrode active material layer to increase the capacity of the positive electrode and improve the life characteristics of the battery.
[0023] The metal oxide additive promotes the adsorption and desorption of polysulfides and the reaction from long-chain polysulfides to short-chain polysulfides, thereby suppressing the shuttling phenomenon of polysulfides.
[0024] The metal oxide additive may include at least one selected from the group consisting of niobium tungsten oxide, iron oxide, iron hydroxide, titanium oxide, zinc oxide, manganese oxide, nickel oxide, and silicon oxide.
[0025] For example, when the lithium secondary battery is a lithium-sulfur secondary battery, a shuttling phenomenon occurs in which polysulfides diffuse from the positive electrode to the negative electrode due to the sulfur component contained in the positive electrode active material. If the diffusion of polysulfides continues, the capacity of the positive electrode decreases and the life of the battery is shortened. In particular, since polysulfides having long chains have high solubility in organic electrolytes, it is necessary to suppress the shuttling phenomenon of polysulfides that occurs from the positive electrode to the negative electrode through the organic electrolyte. In the positive electrode containing the metal oxide additive, the adsorption and desorption of polysulfides and the reaction from long-chain polysulfides to short-chain polysulfides (Li2S2, Li2S) are promoted, so that the shuttling phenomenon of polysulfides can be suppressed. As a result, the capacity reduction phenomenon of the positive electrode can be minimized and the life characteristics of the battery can be improved.
[0026] Also, the metal oxide additive may be included in an amount of 1 wt% to 10 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the metal oxide additive may be 1 wt% or more, 2 wt% or more, or 3 wt% or more, and 8 wt% or less, 9 wt% or less, or 10 wt% or less. If the content of the metal oxide additive is 1 wt% or less, the effect of improving the capacity and battery life of the positive electrode is negligible, and if it exceeds 10 wt%, the amount of active material in the electrode is reduced, which may cause a problem of reduced capacity.
[0027] In the positive electrode for a lithium secondary battery according to the present invention, the sulfur-carbon composite may be used as a positive electrode active material. The sulfur-carbon composite is a mixture of a carbon material and sulfur to reduce the outflow of sulfur into an electrolyte and to increase the electrical conductivity of an electrode containing sulfur.
[0028] The sulfur-carbon composite may contain sulfur and a carbon material, specifically, the sulfur and the carbon material may be contained in a weight ratio of 55-90:45-10. When the weight ratio of the sulfur and the carbon material contained in the sulfur-carbon composite is satisfied, the capacity of the battery can be improved and the conductivity can be maintained at the same time.
[0029] In addition, the sulfur-carbon composite may be included in an amount of 60 wt % to 95 wt % based on the total weight of the positive electrode active material layer, specifically, 60 wt % or more, 70 wt % or more, or 80 wt % or less, or 93 wt % or less, 94 wt % or less, or 95 wt % or less. If the amount is less than the above range, the battery performance may be deteriorated, and if the amount is more than the above range, the content of the binder and / or metal oxide additive other than the positive electrode active material is relatively reduced, thereby reducing durability, or the effect of improving the capacity of the positive electrode or the life characteristics of the battery is negligible.
[0030] In addition, in the sulfur-carbon composite, the sulfur may be selected from the group consisting of elemental sulfur (S8), a sulfur-based compound, and a sulfur-carbon composite. The sulfur-based compound is specifically Li2S n (n≧1), organic sulfur compounds or carbon-sulfur polymers (C2S x ) n :x=2.5~50, n≧2), etc.
[0031] In addition, in the sulfur-carbon composite, the carbon material may be a porous carbon material, which may be generally prepared by carbonizing various carbon material precursors.
[0032] The porous carbon material includes non-uniform pores, and the average diameter of the pores may be 1 nm to 200 nm, specifically, 1 nm or more, 5 nm or more, or 10 nm or more, or 100 nm or less, 150 nm or less, or 200 nm or less. The porosity or void ratio of the porous carbon material may be 10% to 90% of the total volume of the porous carbon material, specifically, 10% or more, 15% or more, or 20% or more, or 70% or less, 80% or less, or 90% or less. If the average diameter and porosity of the pores are below the above ranges, the size of the pores is merely at the molecular level, and impregnation with sulfur is impossible. Conversely, if they exceed the above ranges, the mechanical strength of the porous carbon is weakened, making it unsuitable for use in the manufacturing process of an electrode.
[0033] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk-like, and is not limited as long as it is generally used in lithium secondary batteries.
[0034] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be one or more selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), and activated carbons, but is not limited thereto. Preferably, the porous carbon material may be graphite.
[0035] In the positive electrode for a lithium secondary battery according to the present invention, the binder may be SBR (Styrene-Butadiene Rubber) / CMC (Carboxymethyl Cellulose), poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, poly(methyl methacrylate), polyvinylidene fluoride, a copolymer of polyhexafluoropropylene and polyvinylidene fluoride (trade name: Kynar), poly(ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polystyrene, polyacrylic acid, and derivatives, mixtures, and copolymers thereof.
[0036] The content of the binder may be 1 to 20 wt%, preferably 3 to 18 wt%, more preferably 5 to 15 wt%, based on the total weight of the positive active material layer. If the content is less than this range, the binding strength between the positive active materials or between the positive active material and the current collector is significantly reduced, and the problem of reduced capacity characteristics can be prevented. In addition, it is expected that the eruption of polysulfide due to the interaction between the polysulfide and the specific functional group of the polymer chain used in the binder can be suppressed. If the content exceeds this range, the battery capacity may be reduced.
[0037] The positive electrode for a lithium secondary battery according to the present invention may further include a conductive material to ensure a lithium ion migration path in the positive electrode.
[0038] The conductive material can form and maintain a conductive structure and pore distribution that can ensure a lithium ion migration path in the positive electrode.
[0039] The conductive material may be one or more selected from the group consisting of carbon black selected from Super P, Denka Black, Acetylene Black, Ketjen Black, Channel Black, Furnace Black, Lamp Black, and Thermal Black; carbon derivatives selected from carbon nanotubes and fullerenes; conductive fibers selected from carbon fibers and metal fibers; metal powders selected from carbon fluoride, aluminum, and nickel powders; and conductive polymers selected from polyaniline, polythiophene, polyacetylene, and polyphenols.
[0040] The conductive material may be included in an amount of 1 wt% to 20 wt% based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material may be 1 wt% or more, 3 wt% or more, or 5 wt% or more, and 15 wt% or less, 18 wt% or less, or 20 wt% or less. If the content is less than this range, it is difficult to form and maintain a conductive structure and a lithium ion migration path throughout the positive electrode active material layer, and the increase in the discharge capacity of the battery and the effect of improving overvoltage are negligible, and if the content exceeds this range, the life of the battery may be shortened.
[0041] In the positive electrode for a lithium secondary battery according to the present invention, the positive electrode current collector is not particularly limited as long as it has high conductivity without causing a chemical change in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In this case, the positive electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, and nonwoven fabric having fine irregularities formed on the surface to enhance adhesion to the positive electrode active material.
[0042] [Method of manufacturing positive electrodes for lithium secondary batteries] The present invention also relates to a method for producing a positive electrode for a lithium secondary battery.
[0043] The method for preparing a positive electrode for a lithium secondary battery may include: (S1) preparing a positive electrode slurry using a sulfur-carbon composite, a binder, and a highly porosity conductive material; and (S2) coating a positive electrode current collector with the positive electrode slurry and drying the same.
[0044] In step (S1), a positive electrode slurry may be prepared using the sulfur-carbon composite, a binder, and a highly porosity conductive material.
[0045] To prepare the sulfur-carbon composite, the carbon material and sulfur are mixed in a specified weight ratio, and then heat-treated at 120° C. to 180° C. for 10 minutes to 1 hour to prepare the sulfur-carbon composite. The specific types and weight ratios of the dot-shaped carbon material and sulfur used are the same as those described above.
[0046] Thereafter, the sulfur-carbon composite, the binder, and the metal oxide-based additive were mixed in a solvent to prepare a positive electrode slurry. The types and amounts of the binder and the metal oxide-based additive used to prepare the positive electrode slurry were the same as those described above.
[0047] The solvent used in preparing the positive electrode slurry may be at least one selected from the group consisting of water (distilled water), methanol, ethanol, isopropyl alcohol, acetone, dimethyl sulfoxide, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, acetic acid, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, and ethyl propionate. In particular, when water (distilled water) or an anhydrous alcohol-based solvent is used, damage to the positive electrode active material can be prevented, which is preferable.
[0048] The concentration of the positive electrode slurry is not particularly limited as long as the coating process can be smoothly performed.
[0049] In the step (S2), the positive electrode slurry is coated on a positive electrode current collector and dried to form a positive electrode active material layer, thereby manufacturing a lithium secondary battery.
[0050] [Lithium secondary battery] The present invention also relates to a lithium secondary battery comprising a positive electrode as described above.
[0051] The lithium secondary battery according to the present invention may include a positive electrode, a negative electrode, a separator interposed therebetween, and an electrolyte.
[0052] In the present invention, the negative electrode of the lithium secondary battery may include a negative electrode current collector and a negative electrode active material layer having a negative electrode active material formed on the negative electrode current collector.
[0053] The negative electrode active material may be, for example, a carbon material capable of absorbing and releasing lithium metal or lithium ions, silicon, or tin. The carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. In this case, the negative electrode may include a binder, and various types of binder polymers such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, and polymethylmethacrylate may be used as the binder.
[0054] In addition, the negative electrode current collector is not particularly limited as long as it is conductive without causing a chemical change in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or a copper or stainless steel surface treated with carbon, nickel, titanium, silver, or an aluminum-cadmium alloy, etc. In addition, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, and nonwoven fabric having fine irregularities formed on the surface, similar to the positive electrode current collector.
[0055] In this case, the negative electrode active material layer may further include a binder, a conductive material, a filler, and other additives.
[0056] The binder is used to bind the electrode active material and the conductive material and to bind the electrode active material to the current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0057] The conductive material is used to further improve the conductivity of the electrode active material. The conductive material is not particularly limited as long as it has conductivity without causing a chemical change in the battery, and examples of the conductive material include graphite such as natural graphite or artificial graphite, carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fiber and metal fiber, metal powders such as carbon fluoride, aluminum, and nickel powder, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and polyphenylene derivatives.
[0058] The filler is selectively used as a component that suppresses the expansion of the electrode, and is not particularly limited as long as it is a fibrous material that does not cause chemical changes to the battery. For example, fibrous materials such as olefin polymers such as polyethylene and polypropylene; glass fiber, and carbon fiber are used.
[0059] In the present invention, the separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in electrochemical devices, such as, but not limited to, a polyolefin-based porous membrane or nonwoven fabric.
[0060] Examples of the polyolefin-based porous membrane include membranes formed of olefin-based polymers such as polyethylene (high density polyethylene, linear low density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene), polypropylene, polybutylene, and polypentene, each of which is used alone or in combination.
[0061] In addition to polyolefin-based nonwoven fabrics, the nonwoven fabrics may be made of, for example, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalene, etc., either alone or as a mixture of polymers. The structure of the nonwoven fabric may be a spunbonded nonwoven fabric or a meltblown nonwoven fabric made of long fibers.
[0062] The thickness of the porous substrate is not particularly limited, but is from 1 μm to 100 μm, or from 5 μm to 50 μm.
[0063] The size of the pores present in the porous substrate and the porosity are not particularly limited, but may be 0.001 μm to 50 μm and 10% to 95%, respectively.
[0064] In the present invention, the electrolyte may be a non-aqueous electrolyte, and the electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt may be any of those commonly used in electrolytes for lithium secondary batteries without any limitations. For example, the lithium salt may be LiFSI, LiPF6, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiPF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, and lithium 4-phenylborate.
[0065] The organic solvent contained in the non-aqueous electrolyte may be any organic solvent commonly used in electrolytes for lithium secondary batteries, and may be used without limitation, such as ethers, esters, amides, linear carbonates, and cyclic carbonates, which may be used alone or in combination of two or more. Among these, representative examples include cyclic carbonates, linear carbonates, and carbonate compounds that are slurries thereof.
[0066] Specific examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or slurries of two or more of these. Examples of these halides include, but are not limited to, fluoroethylene carbonate (FEC).
[0067] In addition, specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a slurry of two or more of these. In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are high-viscosity organic solvents with high dielectric constants and can dissociate lithium salts in the electrolyte better, and by mixing such cyclic carbonates with linear carbonates with low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution with higher electrical conductivity can be prepared.
[0068] In addition, the organic solvent may be, but is not limited to, any one or more of ethers selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, and ethyl propyl ether.
[0069] In addition, the ester among the organic solvents may be any one or two or more selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, but is not limited thereto.
[0070] The injection of the non-aqueous electrolyte may be performed at an appropriate stage during the manufacturing process of the electrochemical device depending on the manufacturing process and required properties of the final product, i.e., before assembly of the electrochemical device or at the final stage of assembly of the electrochemical device.
[0071] The lithium secondary battery according to the present invention can be manufactured by a lamination (stack) and folding process of the separator and the electrode in addition to a general winding process.
[0072] The shape of the battery case is not particularly limited, and may be various shapes such as a cylindrical shape, a laminated shape, a square shape, a pouch shape, a coin shape, etc. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted.
[0073] In addition, the lithium secondary battery can be classified into various types of batteries such as a lithium-sulfur secondary battery, a lithium-air battery, a lithium-oxide battery, and a lithium solid-state battery depending on the cathode / anode materials used.
[0074] The present invention also provides a battery module including the lithium secondary battery as a unit cell.
[0075] The battery module can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.
[0076] Examples of the medium- to large-sized devices include, but are not limited to, power tools powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0077] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of the present invention. It is natural that such changes and modifications fall within the scope of the accompanying claims.
[0078] [Example 1: Manufacture of a positive electrode for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery] (1) Cathode manufacturing Sulfur and carbon nanotubes, a carbon material, were mixed in a weight ratio of 75:25 and then heat-treated at 155°C for 30 minutes to produce a sulfur-carbon composite.
[0079] 90 wt% of the sulfur-carbon composite, 5 wt% of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3 (w / w)) as a binder, and 5 wt% of niobium tungsten oxide as a metal oxide additive were mixed and dissolved in water to prepare a cathode slurry having a concentration of 20% based on the solid content.
[0080] The positive electrode slurry was coated on an aluminum current collector to form a positive electrode active material layer, which was then dried and rolled to prepare a positive electrode.
[0081] (2) Manufacturing of lithium-sulfur secondary batteries The prepared positive electrode was used as the positive electrode, lithium metal was used as the negative electrode, and the electrolyte was prepared using a mixed solvent of 2-MF / DME (33:77, v / v) containing 3 wt% LiNO3 (2-MF: 2-methylfuran, DME: dimethoxyethane) and a porous polyolethylene separator to prepare a pouch cell type lithium-sulfur secondary battery.
[0082] [Example 2] A positive electrode and a lithium-sulfur secondary battery were manufactured in the same manner as in Example 1, except that the content of niobium tungsten oxide, which is a metal oxide additive, was 3 wt %.
[0083] [Example 3] A positive electrode and a lithium-sulfur secondary battery were manufactured in the same manner as in Example 1, except that the content of niobium tungsten oxide, which is a metal oxide additive, was 1 wt %.
[0084] [Comparative Example 1] A positive electrode and a lithium-sulfur secondary battery were manufactured in the same manner as in Example 1, except that niobium tungsten oxide was not used in the manufacture of the positive electrode.
[0085] [Experimental Example 1: Analysis of performance improvement effect of lithium-sulfur secondary battery] The performance of the lithium-sulfur secondary batteries prepared in the examples and comparative examples was examined, and the results are shown in Table 1 below.
[0086] (1) Discharge capacity evaluation The lithium-sulfur secondary batteries prepared in the examples and comparative examples were discharged at 0.1 C to 1.8 V in CC (Constant Current) mode at 25° C., and then charged to 2.5 V at a constant current of 0.1 C, and the discharge capacities were measured and compared.
[0087] (2) Life performance evaluation The battery for which the discharge capacity evaluation experiment was performed was discharged at 0.5 C to 1.8 V in CC (Constant Current) mode at 25° C., and then charged to 2.5 V at a constant current of 0.2 C to evaluate the life performance.
[0088] [Table 1]
[0089] As a result, as shown in Table 1, Examples 1 and 2 were shown to be excellent in both discharge capacity and life characteristics.
[0090] In Example 3, the content of the metal oxide-based additive was further reduced compared to Examples 1 and 2, and although the discharge capacity was similar, it was shown that it was not possible to operate the battery until the life characteristics were measured.
[0091] Comparative Example 1 shows similar results to Example 3, as it does not contain any metal oxide additive.
[0092] FIG. 1 is a graph showing the results of measuring the discharge capacity of lithium-sulfur secondary batteries including the positive electrodes prepared in Example 1 and Comparative Example 1.
[0093] As shown in FIG. 1, when comparing the available 0.5C discharge capacity, it can be seen that Example 1 has a capacity of 930 mAh / g and Comparative Example 1 has a capacity of 255 mAh / g.
[0094] FIG. 2 is a graph showing the results of measuring the life characteristics of lithium-sulfur secondary batteries including the positive electrodes prepared in Example 1 and Comparative Example 1, respectively.
[0095] As shown in FIG. 2, it was found that Example 1 could be driven for 300 cycles or more, whereas Comparative Example 1 could not be driven.
[0096] From these results, it was confirmed that adding a certain amount of metal oxide-based additive to the positive electrode of a lithium-sulfur secondary battery can improve the discharge capacity and life characteristics of the battery.
[0097] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is understood that various modifications and variations can be made by those having ordinary skill in the art to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the following claims.
Claims
1. In a positive electrode for a lithium secondary battery including a positive electrode active material layer, The positive electrode active material layer includes a sulfur-carbon composite as a positive electrode active material, a binder, and a metal oxide additive, The metal oxide additive is niobium tungsten oxide, The metal oxide additive is contained in an amount of 3 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
2. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the binder comprises at least one selected from the group consisting of SBR (Styrene-Butadiene Rubber) / CMC (Carboxymethyl Cellulose), poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, poly(methyl methacrylate), polyvinylidene fluoride, copolymers of polyhexafluoropropylene and polyvinylidene fluoride, poly(ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polystyrene, polyacrylic acid, and derivatives, mixtures, and copolymers thereof.
3. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the positive electrode active material layer is formed on at least one surface of a positive electrode current collector.
4. 4. The positive electrode for a lithium secondary battery according to claim 3, wherein the positive electrode current collector comprises stainless steel, aluminum, nickel, titanium, or calcined carbon.
5. A lithium secondary battery comprising the positive electrode according to claim 1, a negative electrode, and an electrolyte solution.
6. 6. The lithium secondary battery according to claim 5, wherein the negative electrode comprises lithium metal.
7. 6. The lithium secondary battery according to claim 5, wherein the lithium secondary battery is a lithium-sulfur secondary battery.
8. The lithium secondary battery according to claim 5 , wherein the lithium secondary battery is a pouch-type lithium secondary battery.
Citation Information
Patent Citations
JP2004‐179160B
Method for producing iron hydroxide (FeOOH) and cathode for lithium-sulfur battery containing iron hydroxide
JP2019531243A
KR2015‐0046861
Current collector having easily adhering layer, electrode, all-solid-state secondary battery, electronic device, electric vehicle, and methods for manufacturing current collector having easily adhering layer, electrode and all-solid-state secondary battery
WO2019230592A1